Phloem anatomy predicts berry sugar accumulation across 13 wine-grape cultivars - Stanfield, Ryan C.; Forrestel, Elisabeth J.; Elmendorf, Kayla E.; Bagshaw, Sophia B.; Bartlett, Megan K. (Frontiers in Plant Science, 2024)
Climate change is impacting the wine industry by accelerating ripening processes due to warming temperatures, especially in areas of significant grape production like California.Increasing temperatures accelerate the rate of sugar accumulation (measured in ⁰Brix) in grapes, however this presents a problem to wine makers as flavor profiles may need more time to develop properly. To alleviate the mismatch between sugar accumulation and flavor compounds, growers may sync vine cultivars with climates that are most amenable to their distinct growing conditions. However, the traits which control such cultivar specific climate adaptation, especially for ⁰Brix grape sugar accumulation rate, are poorly understood. Recent studies have shown that higher rates of fruit development and sugar accumulation are predicted by larger phloem areas in different organs of the plant. Here we test this hypothesis using a common garden experiment in the Central Valley of Northern California using 18 cultivars of the common grapevine (Vitis vinifera) and assess the grape berry sugar accumulation rates as a function of phloem area in leaf and grape organs. We find that phloem area in the leaf petiole organ as well as the berry pedicel is a significant predictor of ⁰Bbrix accumulation rate across cultivars and that grapes from warm climates overall have larger phloem areas than those from hot climates. In contrast, other physiological traits such as photosynthetic assimilation and leaf water potential did not predict berry accumulation rates. As hot climate cultivars have lower phloem areas which would slow down brix accumulation, growers may have inadvertently been selecting this trait to align flavor development with sugar accumulation across the common cultivars tested. This work highlights a new trait that can be easily phenotyped (i.e., petiole phloem area) and be used for growers to match cultivar more accurately with the temperature specific climate conditions of a growing region to obtain satisfactory sugar accumulation and flavor profiles.